Sedentary Lifestyle Berhubungan dengan Status Gizi pada Remaja - Aulia, Syifa Nurul; Sukmawati, Sukmawati; Rosidin, Udin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between a sedentary lifestyle and nutritional status in adolescents at SMPIT Qordova. The method used is correlation analysis with a cross-sectional approach. The research results show that the p-value is 0.000 (p < 0.05) with a correlation coefficient of 0.405, which means there is a relationship in the same direction with moderate strength. In conclusion, a significant relationship exists between sedentary lifestyle and nutritional status in adolescents at SMPIT Qordova. Keywords: Adolescents, Sedentary Lifestyle, Nutritional Status